The Role of Indonesian Literature in the Young Generation - Hanifa, Nuha Sekar; Putri, Nina Queena Hadi (Universitas Syiah Kuala, 2025)
Indonesian literature has various types, ranging from poetry, prose, to drama, which reflect the nation's culture and values. As the successor of the nation, the younger generation has an obligation to maintain and develop Indonesian literature. However, due to technological developments and the influence of foreign cultures, the interest of the younger generation in literature is often overlooked. Therefore, it is important to understand how literature affects human life. Literature is an important part of Indonesian culture that reflects the nation's history, values, and identity. In this modern era, literature plays a major role in shaping the character and insight of the younger generation (Scott, 2014). However, with the challenges of digitization and a shift in interest in instant content, literature must change to remain relevant. This study uses a qualitative approach. Therefore, it is very important that the younger generation plays an important role in cultivating Indonesian literature which is very beautiful and has a lot of artistic diversity. The attention of the younger generation to literature is often distracted in the challenging digital era. Therefore, it is very important to develop new ways of delivering literature, such as using digital platforms and holding interesting literacy programs. If the community, teachers, and the government work together, Indonesian literature can remain relevant and interesting for the younger generation. This will allow them to become agents of change that can preserve and develop Indonesia's literary wealth in the future.